2021
DOI: 10.1038/s42003-021-02484-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic divergence during feralization reveals both conserved and distinct mechanisms of parallel weediness evolution

Abstract: Agricultural weeds are the most important biotic constraints to global crop production, and chief among these is weedy rice. Despite increasing yield losses from weedy rice in recent years worldwide, the genetic basis of weediness evolution remains unclear. Using whole-genome sequence analyses, we examined the origins and adaptation of Japanese weedy rice. We find evidence for a weed origin from tropical japonica crop ancestry, which has not previously been documented in surveys of weedy rice worldwide. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(55 citation statements)
references
References 66 publications
(83 reference statements)
2
53
0
Order By: Relevance
“…is an especially good study model for revealing the effects of hybridization on the effective combinations of adaptive alleles given its very close relationship to the genomic model cultivated rice (O. sativa L.) and its set of wild-like traits. In general, weedy rice has evolved independently multiple times from domesticated ancestors, and this evolution has been confirmed from four different cultivated rice subgroups: temperate japonica (hereafter, TEJ), tropical japonica (TRJ), indica (IND) and aus (AUS) (Li et al, 2017;Qiu et al, 2017;Vigueira et al, 2019;Sun et al, 2019;Qiu et al, 2020;Imaizumi et al, 2021). In Japan, two major morphotypes exist: black-hull (BH) and strawhull (SH); these morphotypes are classified based on hull colour.…”
mentioning
confidence: 96%
“…is an especially good study model for revealing the effects of hybridization on the effective combinations of adaptive alleles given its very close relationship to the genomic model cultivated rice (O. sativa L.) and its set of wild-like traits. In general, weedy rice has evolved independently multiple times from domesticated ancestors, and this evolution has been confirmed from four different cultivated rice subgroups: temperate japonica (hereafter, TEJ), tropical japonica (TRJ), indica (IND) and aus (AUS) (Li et al, 2017;Qiu et al, 2017;Vigueira et al, 2019;Sun et al, 2019;Qiu et al, 2020;Imaizumi et al, 2021). In Japan, two major morphotypes exist: black-hull (BH) and strawhull (SH); these morphotypes are classified based on hull colour.…”
mentioning
confidence: 96%
“…NWR and other inbred populations (IND, AUS, TEJ and TRJ) are all self‐pollinating species, but the diversity and heterozygous ratio of WR was typically higher at the morphological and genetic levels, suggesting the possibility of introgression. This finding also revealed that introgression plays important roles in the evolution of weedy rice from locally introduced modern cultivars 34,38,39 …”
Section: Discussionmentioning
confidence: 66%
“…This finding also revealed that introgression plays important roles in the evolution of weedy rice from locally introduced modern cultivars. 34,38,39 Although the trace of WR spread cannot be determined using morphological data, molecular genetic programs such as "TESS" 40 visualize dispersion of the clusters by interpolation of genetic coefficients and projection onto a map of Nicaragua, which reveals trends among accessions across long distances. In this study, three different contamination types of WR, namely seeds, pollen-mediated gene flow and WR plants from a soil seedbank, were identified by tracing the dispersal patterns in specific regions.…”
Section: Discussionmentioning
confidence: 99%
“…SH_TEJ weedy rice showed the deepest seed dormancy among the weedy rice types evaluated in this study although the weeds were derived from hybridization with cultivated rice (Imaizumi et al, 2021), which must be a non-adaptive parent for weedy-like traits, including seed dormancy. Seed dormancy in cereal crops should be moderate because high seed dormancy impairs the establishment of crops, and a lack of seed dormancy causes preharvest sprouting, significantly reducing the yield and quality (Rodríguez et al, 2015; Tuan et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…In Japan, two major morphotypes exist: black-hull (BH) and strawhull (SH); these morphotypes are classified based on hull colour. Whole genome sequence analyses have revealed that Japanese weedy rice can be classified into three groups: TEJ-derived BH weedy rice, TEJ-derived SH weedy rice, and TRJ-derived SH weedy rice (hereafter BH, SH_TEJ and SH_TRJ, respectively), with SH_TEJ weedy rice evolving from the hybridization between BH weedy rice and cultivated rice (Imaizumi et al, 2021). The hybrid-derived weedy rice strains display crop-like adaptive traits, such as shorter plant height, which facilitates crop mimicry, as well as a critical weedy-like trait, namely deep seed dormancy.…”
Section: Introductionmentioning
confidence: 99%